2000
DOI: 10.4315/0362-028x-63.11.1551
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Biogenic Amines in Raw Milk Hispánico Cheese Manufactured with Proteinases and Different Levels of Starter Culture

Abstract: Two proteinases, a neutral proteinase from Bacillus subtilis and a cysteine proteinase from Micrococcus sp., were used to accelerate the ripening process of raw cow's milk Hispánico cheese, a semihard variety. Two levels (0.1% and 1%) of a commercial starter culture containing Lactococcus lactis subsp. lactis and L. lactis subsp. cremoris were added for cheese manufacture. The influence of both factors, proteinase addition and level of starter culture, on the growth of amino acid-decarboxylating microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 14 publications
2
36
2
4
Order By: Relevance
“…In conclusion, comparing the obtained results with processed cheeses consumed in Egypt exceeded the permissible value (10 mg%) which seemed to pose a threat to public health. Nearly, similar results were recorded by Fernandez-García et al (2000). While, higher results were obtained by Jarisch (2004) in Gouda cheese samples.…”
Section: Discussionsupporting
confidence: 73%
“…In conclusion, comparing the obtained results with processed cheeses consumed in Egypt exceeded the permissible value (10 mg%) which seemed to pose a threat to public health. Nearly, similar results were recorded by Fernandez-García et al (2000). While, higher results were obtained by Jarisch (2004) in Gouda cheese samples.…”
Section: Discussionsupporting
confidence: 73%
“…It has been shown that there is a good relationship between the C t value and the content of histamine detected by HPLC, although the samples analysed were very different in terms of origin and treatment of milk or proteolysis and ripening periods, factors that have a strong influence on the final content of BA in the product (Ordoñez et al, 1997;Fernández et al, 2007;Fernández-García et al, 2000). When more homogeneous groups were analysed, a different and accurate threshold value could be defined.…”
Section: Discussionmentioning
confidence: 95%
“…The accumulation of BAs in dairy products occurs at later stages of the process, when the substrate amino acids are released from casein (9). In the case of yogurt, where S. thermophilus is one of the two starter species normally used, the process consists of a rapid acidification that is performed at 42°C, followed by refrigeration (4°C) until consumption.…”
Section: Resultsmentioning
confidence: 99%